The Global South's Agenda for World Trade Organization (WTO) Reform: A Case Study of the G20 and BRICS - Saepudin, Saepudin; Pratama, Indrasyifa Chaliq; Audrei, Fanesya; Wibowo, Caesar Andrea Ari (Universitas Al-azhar Indonesia, 2024)
This article will analyze the agenda of the Global South in responding to the inability of the World Trade Organization (WTO) to solve contemporary international trade problems. Global South countries are uniting to ensure the interests of developing countries are recognized in the WTO decision process. Global South thinking itself offers an alternative in International Relations, focusing on economic inequality and Global North-South relations. Descriptive qualitative research methods are used to analyze the existence of South-South cooperation in an effort to reform the WTO. Global South countries such as China, India, and Brazil actively participate in the WTO and G20 to fight for their interests and reduce the gap with the Global North through South-South Cooperation. Through WTO reforms, they seek to change the Global North-dominated global governance, building a new trade architecture based on equality and shared development. Brazil as the 2024 G20 Presidency and the BRICS play an important role in supporting WTO reforms for fair trade and development, so Global South collaboration is key in creating positive change in international trade governance.Keywords: Global Governance, Global South, Global North, WTO reform.